Muscle activity and power output recovery: the roles of rest duration and underlying endurance capacity in the wingate test - Hu, Yuxiao; Liu, Weijun; Duan, Qingqing; Gong, Zhigang (Frontiers in Physiology, 2025)
PurposeThis study aimed to determine the optimal recovery time for maximizing post-activation performance enhancement in resistance-trained males grouped by local muscle endurance, and evaluate its effects on anaerobic performance and neuromuscular activity.MethodsTwenty-four healthy men were grouped by repetitions completed at 80% of 1 repetition maximum (1RM) back squat, serving as a functional proxy for muscle endurance characteristics: Low-Muscle-Endurance (LME, n = 8, 20.5 ± 1.2 years), Intermediate-Muscle-Endurance (IME, n = 8, 20.3 ± 1.3 years), and High-Muscle-Endurance (HME, n = 8, 20.1 ± 1.1 years). Participants completed a control session (CON) and three experimental trials involving a back squat conditioning protocol (3 × 3 repetitions at 80% 1RM), followed by a 30-s Wingate Anaerobic Test (WAnT) after 3 (T3), 8 (T8), or 12 (T12) minutes of recovery. Surface electromyography (EMG) signals were recorded from the right rectus femoris (RF), biceps femoris (BF), and gastrocnemius lateralis (GL) during WAnT and analyzed for integrated EMG (IEMG) and mean power frequency (MPF).ResultsA clear hierarchy in baseline peak power (PP) was observed across groups, with LME > IME > HME (all p < 0.05). The LME group also demonstrated a higher fatigue index (FI) than both HME and IME groups (all p < 0.05). Regarding the time course of PAPE, PP for the cohort was significantly higher at T12 than at CON (p = 0.021). RF IEMG at T12 was significantly elevated versus CON (p = 0.024), while BF IEMG increased at T8 (p = 0.011). BF MPF was also higher at T12 compared to CON (p = 0.039). No significant recovery effects were observed for mean power (MP).ConclusionIndividuals stratified by local muscle endurance exhibited distinct baseline anaerobic capacities and fatigue profiles. The optimal PAPE window occurred 8–12 min post-activation, marked by initial biceps femoris neural drive enhancement, followed by peak power and improved neuromuscular efficiency at 12 min. These findings support this practical stratification method for personalizing recovery strategies, linking PAPE magnitude differences to physiological traits reflected in endurance-based grouping.